2021
DOI: 10.1093/braincomms/fcab066
|View full text |Cite
|
Sign up to set email alerts
|

Early nutrition and white matter microstructure in children born very low birth weight

Abstract: Infants born at very low birth weight (<1500 g) are vulnerable to nutritional deficits during their first postnatal month, which are associated with poor neurodevelopmental outcomes. Despite this knowledge, the impact of early postnatal nutrition on white matter microstructure in children born very low birth weight has not been investigated. In this prospective cohort study, we employed a whole-brain approach to investigate associations between precise estimates of nutrient intake within the first postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
3
5
0
Order By: Relevance
“…Our study extends these findings by showing, in whole-brain MEG analyses, that higher protein and energy intake during the first month of life were associated with increased connectivity in the alpha-frequency band, whereas higher lipid intake was associated with decreased beta-band connectivity. Importantly, the present results complement our previous structural connectivity findings that showed higher intakes of protein and energy during the same postnatal period (days 9–29) were associated with improved white matter microstructure at 5 years of age ( Sato et al, 2021a ). These findings suggest that early macronutrient and energy intakes contribute to the maturation of both functional and structural connectivity in the preterm brain.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study extends these findings by showing, in whole-brain MEG analyses, that higher protein and energy intake during the first month of life were associated with increased connectivity in the alpha-frequency band, whereas higher lipid intake was associated with decreased beta-band connectivity. Importantly, the present results complement our previous structural connectivity findings that showed higher intakes of protein and energy during the same postnatal period (days 9–29) were associated with improved white matter microstructure at 5 years of age ( Sato et al, 2021a ). These findings suggest that early macronutrient and energy intakes contribute to the maturation of both functional and structural connectivity in the preterm brain.…”
Section: Discussionsupporting
confidence: 89%
“…Significant results were also found in the alpha-frequency band, suggesting shared mechanisms by which protein and energy impact resting-state networks underlying cognitive and socio-cognitive functions. This is further supported by our previous diffusion MRI study that found significant associations between protein and energy intake with DTI metrics within many overlapping white matter tracts ( Sato et al, 2021a ). Early protein intake is essential for synaptogenesis and myelination, which undergoes critical development during the preterm period ( Georgieff, 2007 ; Cormack et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Breast milk contains nutrients that are essential in early infancy, including docosahexaenoic acid (DHA) and long-chain polyunsaturated fatty acids (LC-PUFAs) [ 13 , 14 ]. Emerging studies suggest that breast milk feeding in infancy is associated with improved brain growth, white matter microstructure, and short- and long-term neurodevelopmental performance in preterm infants [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research has been underpowered and short-term in design. The interrelationship between nutrition, growth, and neurodevelopmental outcomes reported in these studies can only be interpreted as associative, not causative and results are rarely conclusive (22)(23)(24)(25). There is lack of good quality evidence upon which to base neonatal nutrition practice, leading to clinician opinion or consensus rather than gold standard evidence governing decisions around neonatal nutritional care (26).…”
Section: Introductionmentioning
confidence: 99%